Human values in Bachelor's degree in Nursing’s students - Héctor Cabrera Rodríguez; Zenia Tamara Sánchez García; Ivette Mullens Ramos; Liumys Zayas Alzamora; Ernesto Julio Bernal Valladares; Isys Leyva Betancourt (Medisur)
Foundation: the quality in the nursing professionals’ training depends not only on the knowledge and skill systems that are identified and developed in the curriculum, but also on the set of values that are formed in them. Objective: determine the human values current state in second-year students of the Bachelor's Degree in Nursing at the Cienfuegos Medical Sciences University. Methods: a cross-sectional descriptive study was carried out on a 52 students and seven teacher’s population. A survey was applied to the students and an observation guide; In addition, an interview was carried out with the professors who teach in said academic year, the Kappa value was used as a statistical procedure. Results: 86.5% of the students consider that they have developed the value solidarity, humanism is present in 84.6%, while the least identified values were anti-imperialism indicated by 57.6% and internationalism, only by 50.0% of the sample studied. 80 % of teachers consider that students' values are poorly developed. Conclusions: the current state of values in students of the bachelor's degree in nursing shows little development. Strategies must be drawn up based on improvements in their human and professional quality.